A capacidade empreendedora na criação de valor em empresas investidas por fundos de investimento em participações - Cavalheiro Neto, Heitor de Vargas (2020)
The aim of this work is to identify the role of entrepreneurial capability in the value creation in companies invested by equity funds. Different authors show that the entrepreneurial capability may be central to define the creation of value or the frustration in doing so, being the former the main reason of being of a equity fund. To achieve this goal the work starts presenting na overview of the investment funds environment of private owned organizations and their role and importance, which is followed by an analysis of value creation in invested organizations. To substance the work it is presented a brief overview of the Theory of the Growth of the Firm, the development of the Resource Based View, addressing specifically tangible and intangible resources, as well as capabilities, and focus on the analyzes of the the entrepreneur, entrepreneurship and the entrepreneurial capability and its dimension, and its combination with strategic management; and discusses the importance of the business model in supporting the entrepreneurial capability. The objective of this study is to develop a deep understanding of the role of the entrepreneurial capability in the value creation in invested companies, bringing clarity to the role of the entrepreneur and the strategic manager and advance in the study of the entrepreneurial capability investigating a possible change in the balance among its dimensions and eventually the incorporation of new dimensions. With the analysis of the interviews we intend to answer the question of this project: what is the role of entrepreneurial capability in creating value in invested companies by equity funds?